Role of reduced geometry on critical spin-crossover behavior in molecular magnet: Monte Carlo simulation - Yongyut Laosiritaworn (2018)
In this work, the magnetic spin-crossover (SC) behavior was investigated using Monte Carlo simulation. The investigated SC structures were hexagonal films where each molecular magnetic spin was represented by the Ising spins interacting with neighboring spins with short-ranged exchange-type interaction and long-ranged mechano-elastic interaction. The SC spins were mobile but under spring-type interaction constraint. Monte Carlo simulation was used to attain the system mechanical equilibrium, and used to update spin configurations via the modified Wolff algorithm. With varying the films thickness, the radius ratio of the high-spin-state to the low-spin-state, and the system temperature, the thermal equilibrium magnetization was measured to extract the magnetic profiles as well as the fourth order cumulant of the magnetization. The critical temperature T c was extracted via the cumulant-crossing extrapolated to the thermodynamic limit. From the simulation, the magnetization and magnetic susceptibility profiles were obtained as functions of temperature for films thickness ranging from one to four layers. The results show that with increasing films thickness the critical temperature increases due to stronger average short-ranged magnetic interaction. In addition, the greater radius ratio of the high-spin-state to the low-spin-state enhances the phase transition point since higher thermal energy level is required to compensate the larger thermodynamic work required by the volume changed. These results are in agreement with previous studies. The scaling relationship among the critical point, the radius ratio, and films thickness was also successfully proposed. With good statistical accuracy, this scaling formalism can then be used as qualitative guidelines to predict magnetic critical behaviors for further enhanced investigation or for designing desired functional SC applications. © 2013 Elsevier Ltd. All rights reserved.